Kearifan Lokal ‘Orang Pulo’ dalam Tradisi Ngaplus Imah - Prijana .; Dadang Sugiana (PANTUN, 2019)
The tradition of ngaplus imah of Pulo people has been conducted until the eighth generation todays. The Pulo people reside in Cangkuang Village of Leles District of Garut Regency, West Java. The Pulo people are able to maintain six houses of the ancestral heritage, no more and no less. The grounded research shows that the Pulo people admit the children right as heirs of the inheritance. The inheritance right for the Pulo is the right to inhabit not to own the heritage. The occupancy right is not a resolution in the form of structure, but an offerdable rights for girls not boys. They consider that if one of the parents dies then the right to occupy is given to the children. The research concludes that the implementation of Ngaplus Imah tradition has ups and downs. It is sometimes desirable, sometimes less desirable, sometimes complicated, sometimes smooth andsurviving through the local wisdom.Keywords: ngaplus imah, inheritance right, occupancy right, local wisdom